Remarks at the Fifteenth East Asia Summit - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the Coronavirus (COVID-19) pandemic and economic shutdowns that are causing the world’s deepest recession since World War II and the first major recession in ASEAN countries since the 1997 Asian devaluation crisis. He mentioned that women are faring worse in the crisis than men across most countries and across several dimensions including loss of jobs, decline in remittances, food insecurity, and the heavy burden of caregiving responsibilities. He explained that the World Bank Group has moved rapidly to deploy its full financial capacity with much of it going to the poorest countries and to private sectors for trade finance and working capital. He highlighted that the World Bank made available up to twelve billion US dollars of fast-track financing to client countries for them to choose, purchase and deploy Coronavirus (COVID-19) vaccine. He spoke about the DSSI debt service suspension initiative, which he called a good first step, but the relief so far has been less than anticipated because not all creditors participated. The World Bank Group is working on effective approaches for debt reduction and debt resolution to address low income countries’ unsustainable debt burdens. Countries will need to prepare for a different economy post-COVID, by allowing capital, labor, skills and innovation to move into new businesses and sectors. The World Bank strongly supports trade facilitation measures to encourage greater flows across borders.